(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The analysis of process of motion of concrete mixture is executed on a pipeline and dependence is offered for determination of the productivity of solution is a concrete pump (concrete pumps). Calculation data over of technological parameters of process of portage of concrete mixtures are brought taking into account the productivity of machines and diameters of pipelines. Keywords: concrete pump, concrete mixture, transport pipeline, middle speed, viscidity, mobility.